2002
DOI: 10.1074/jbc.m105403200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Profile Induced by Hepatocyte Nuclear Factor 4α in Hepatoma Cells Using an Oligonucleotide Microarray

Abstract: Hepatocyte nuclear factor 4␣ (HNF-4␣), a liver-specific transcription factor, plays a significant role in many liver-specific functions, including lipid, glucose, drug, and ammonia metabolism, and also in embryonal liver development. However, its functions and regulation are not yet clearly understood. In this study, we constructed an adenovirus vector carrying rat HNF-4␣ cDNA and transfected the adenovirus to human hepatoma cells, HuH-7, to enforce expression of the exogenous HNF-4␣ gene. We analyzed HNF-4␣-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 45 publications
4
57
2
Order By: Relevance
“…19,20 In short, HNF4␣-forced reexpression decreased the population of stem/progenitor cells in hepatoma cells and destroyed self-renewal of CSCs by targeting against these important signaling pathways. Consistent with results reported by Naiki et al, 21 we witnessed a list of elevated genes that are indicators for hepatocyte maturation along with proliferative suppression. Moreover, the ammonia detoxification function was also enhanced by HNF4␣ overexpression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…19,20 In short, HNF4␣-forced reexpression decreased the population of stem/progenitor cells in hepatoma cells and destroyed self-renewal of CSCs by targeting against these important signaling pathways. Consistent with results reported by Naiki et al, 21 we witnessed a list of elevated genes that are indicators for hepatocyte maturation along with proliferative suppression. Moreover, the ammonia detoxification function was also enhanced by HNF4␣ overexpression.…”
Section: Discussionsupporting
confidence: 80%
“…24 HNF4␣ has already been shown to increase expression of the p21 gene by antagonizing cMyc activation. 21,25,26 Furthermore, for control of apolipoprotein C III expression, a competition is present between c-Myc and HNF4␣, indicating that HNF4␣ and c-Myc compete for control of the genes involved in cell proliferation as well as differentiation. 27 In our study, we demonstrated that both protein p21 and apolipoprotein C III were raised in hepatoma cells along with increased HNF4␣ expression.…”
Section: Discussionmentioning
confidence: 99%
“…HNF4A is produced from an early stage in hepatocyte differentiation and plays a key role in regulation of liver development and metabolic function; nearly half of the transcribed genes in the liver, including Pck2, are thought to be controlled by HNF4A [34][35][36]. Overexpression of Hnf4a in cell culture results in stimulation of Pck2 transcription [37]. Conversely, Hnf4a liver-specific knockout mice fail to induce PCK2 during fasting [35].…”
Section: Discussionmentioning
confidence: 99%
“…137 Combined with available genetic, biochemical, and gene array data, these results suggest that HNF4␣ is a central determinant of hepatocyte function and differentiation and is crucial for establishing normal liver architecture during development. 139,145,146 In mammals, maturation of the liver is further complicated by the fact that the fetal hepatic environment is also the site of hematopoiesis between E11.5 and E16.5. In this regard, there appears to be a close relationship between hematopoietic cells and the developing hepatic parenchyma, which is governed by cytokine signaling.…”
Section: What Governs the Establishment Of Hepatic Architecture And Mmentioning
confidence: 99%